2008
DOI: 10.1016/j.rmed.2007.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of lung cancer in patients with connective tissue diseases: A 10-year hospital based study

Abstract: The majority of CTD patients who developed LC were diagnosed at advanced stage and had poor survival. Efforts for early detection of LC in CTD patients' group are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 22 publications
2
24
1
Order By: Relevance
“…The higher incidence of lung cancer in patients with connective tissue diseases and the changes in smoking habits should be recognised [22,23]. We were unable to collect smoking habits data for 20 years period.…”
Section: Discussionmentioning
confidence: 99%
“…The higher incidence of lung cancer in patients with connective tissue diseases and the changes in smoking habits should be recognised [22,23]. We were unable to collect smoking habits data for 20 years period.…”
Section: Discussionmentioning
confidence: 99%
“…The causes of lymphopenia in cancer patients may vary. It may result in part from the destruction of lymphocytes by the tumor, and/or from impaired differentiation of lymphocyte progenitors [23]. Peripheral blood lymphopenia is a recognized predictor of poor survival in patients with advanced cancer, attributed to the fundamental role of lymphocytes in cell-mediated immunity with the destruction of host cancer cells [24].…”
Section: Discussionmentioning
confidence: 99%
“…The present case has progressed at an advanced stage of lung cancer when diagnosed. Adžić et al reported that majority of patients who complicated with lung cancer in connective tissue disease (CTD) also presented at an advanced stage of lung cancer with 87% having stage III or IV disease [13] . And they also proposed that the necessity of making efforts for earlier recognition of lung cancer in patients with CTD with regular follow-up, including chest imaging.…”
Section: Discussionmentioning
confidence: 99%